Keanekaragaman Jenis Mangrove di Desa Lalombi Kecamatan Banawa Selatan - Febrianti, Febrianti; Isnainar, Isnainar; Febriawan, Aan; Lilies, Lilies; Buntu, Amalia; Mawaddah, Hayyatun (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the diversity of mangrove species in Lalombi Village, to determine the feasibility of the results of research on mangrove plant species in Lalombi Village, South Banawa District. This type of research is a quantitative descriptive research type and location determination using purposive sampling techniques which are divided into 3 observation stations. Data collection using a modified path method into a transect with zigzag plot placement. The plot used is a tiered plot type with a plot size of 10 × 10 meters for tree observation, a 5 × 5 meter plot for sapling observation, and a 1 × 1 meter plot for sapling observation. This research was conducted in Lalombi Village, South Banawa District, Donggala Regency in September 2024. The results of this study indicate that there are 6 types of mangrove plants in Lalombi Village, namely: Sonneratia alba Smith, Avicennia marina (Forsk.) Vierh, Bruguiera gymnorrhiza (L) Lamk, Ceriops decandra (Griff) Ding Hou, Lumnitzera littorea (Jack) Voigt, Avicennia officinalis L, with a moderate level of diversity (1.76).